Minimally invasive Akin osteotomy and lateral release: Anatomical structures at risk—A cadaveric study. (June 2016) - Yañez Arauz, Juan Manuel; del Vecchio, Jorge Javier; Codesido, Mariano; Raimondi, Nicolás
Highlights: This study analyzed the anatomical relationships and the risks for soft tissue lesions when performing the dorsomedial MIS portal for the Akin osteotomy of the proximal phalanx of the hallux, and the MIS dorsolateral portal for soft tissue release. The possibility of tendon lesion was seen in 12.5% and 18% of cases, the first figure corresponds to EDB detachment. No lesions involving nerves and vessels were reported. The dorso-medial portal must be performed as close as possible to the extensor tendon to reduce the risk of nervous lesion. This type of percutaneous procedures should be conducted by surgeons with experience in foot surgery, and extensive knowledge of the anatomy of the region. Abstract: Background: Among the many surgical techniques used for hallux valgus correction, different osteotomies may be performed in the proximal phalanx as well as lateral release as associated procedures. The aim of this study is to analyze the anatomical relationships and the risks for the soft tissue lessions when performing the dorsomedial minimally invasive surgery (MIS) portal for the Akin osteotomy, and the MIS dorsolateral portal for lateral release, in order to define a safety zone when conducting the procedure in order to avoid complications. Materials and methods: The procedures were carried out on 16 fresh-frozen cadaveric feet. A MIS dorsomedial and dorsolateral portals were performed. The anatomical dissection of the cadaveric pieces was carried out and the different anatomic and surgical relationships were analyzed and measured. Results: No nerve injury was found. Injury of the extensor hallucis longus (EHL) paratendon were seen in 9 cases (56%). There was no injury of the flexor hallucis longus (FHL) tendon and or collateral plantar nerves. A partial injury of the FHL sheath was observed in 44% of the samples. Conclusions: Although percutaneous Akin osteotomy is clinically effective, the possibility of injury of anatomic structures is high (9–55%), however injuries upon vascular or nerve structures were not seen.